Cefaleia crônica diária: classificação, estresse e impacto sobre a qualidade de vida - Galego, José Carlos Busto (2006)
Chronic daily headache (CDH) is a heterogeneous group of headaches that occurs 15 or more days per month, lasting more than four hours, including those associated with medication overuse. The objectives of this study were: to classify Chronic Daily Headache; to assess the quality of life and level of stress of the patients with this type of headache. Casuistic and Method: A hundred patients, from both sexes, with minimum age of 18 years old were prospectively studied. The inclusion criterion was the presence of primary headache with more than 4-hour duration, a frequency of 15 days or more monthly, in the last three months. The diagnosis was according to the second edition of The International Classification of Headache Disorders (ICHD-II) criteria. The SF-36 questionnaire to observe quality of life and Lipp´s Inventory of Stress Symptoms to diagnose stress were used. Patients with chronic organic disease were not included. Results: The patients´ mean age was 38.8 years. The majority (87%) was women. CDH mean duration was 4.0 years. Applying the ICHD-II criteria, 17 different types of diagnosis were necessary to classify CDH. Between these types of diagnosis, 11 presented migraine (80% of the patients). The types with migraine had lower scores according to SF-36 either in physical function (p=0.0015) and social function (p=0.033). A total of 46% of the patients overused medication. Their scores were lower in physical function (p=0.008), bodily pain (p=0.037) and role emotional (p=0.046). Ninety patients presented stress, prevailing the psychological symptoms in 94.5%. Between the patients who presented stress, 2 were at the alert phase, 33 at resistance phase, 46 at almost exhaustion and 9 at exhaustion phase. Stress diminished significantly the scores at the SF-36, except on physical function. There was no association between stress and medication overuse. Comparing the stress phases with SF-36 scores, except on bodily pain scale, the resistance phase showed significant higher scores than the almost exhaustion phase. Conclusions: CDH is the result of a convergence of several types of headaches that integrates the second edition of The International Classification of Headache Disorders. Most patients presented stress and half of them were at the almost exhaustion phase. Stress produced significantly reduction in all scales from SF-36 questionnaire, except on physical function. The patients with stress at the almost exhaustion phase compared with those at the resistance phase showed significant lower scores in all scales of SF-36 questionnaire, except on bodily pain.